Peningkatan Hasil Belajar Melalui Penerapan Metode Demonstrasi Siwa Kelas VIII MTs Al-Huda Tumpuk, Sawoo, Ponorogo - Salsa Bella Agustin; Tamrin Fathoni (https://ejournal.insuriponorogo.ac.id/, 2026)
This study aims to improve fiqh learning using the demonstration method at MTs Al-Huda Tumpuk, Sawoo. This type of research is a literature review.Literature review research is a process of collecting and criticallyexamining literature, journals, articles, books, and other sources ofinformation. Data collection is by taking journals from Google Scholar.Analysis of the journal results of this literature review uses the criticalappraisal method. research results. the conclusion that can be drawn isthat the demonstration method can be an effective method inimproving the learning of fiqh, especially in helping studentsunderstand and apply difficult concepts. However, it should be notedthat the demonstration method must be used judiciously and in theright context to ensure its effectiveness in enhancing the learning of fiqh.